Effect of forefoot and midfoot bending stiffness on agility performance and foot biomechanics in soccer - Brinkmann, D. J.; Koerger, H.; Gollhofer, A.; Gehring, D. (Journal of Applied Biomechanics, 2020)
Footwear bending stiffness is known to positively affect performance in agility maneuvers due to improved energy storage and propulsion based on a stiffer foot-shoe complex. However, the functional properties of the forefoot and midfoot differ. Therefore, the present study investigates the effect of the interface of longitudinal bending stiffness and the ratio of forefoot to midfoot bending stiffness on agility performance and foot biomechanics. A total of 18 male soccer players performed 2 agility tasks in footwear conditions that were systematically modified in forefoot and midfoot bending stiffness. Results revealed that higher longitudinal bending stiffness caused more foot exorotation at the initial ground contact (P < .05), less torsion (P < .001), and an anterior shift in the point of force application during push off (P = .01). In addition, the authors observed decreased forefoot bending (P < .05) and increased torsion (P < .01) in footwear with a higher forefoot-midfoot ratio. Finally, the agility performance was significantly impaired by 1.3% in the condition with the highest forefoot-midfoot ratio (P < .01). The high forefoot-midfoot ratio, that is, a stiff forefoot in combination with a soft midfoot, seemed to shift the flex line from anterior to posterior that may explain the performance impairment.